Jack and Rose as Symbols of Resistance Against Social Stratification in Titanic - Muhammad Alfandi; Theresya Mawar Sharon Irawan; Teofilus Alexander Banjarnahor; Teuku Muhammad Omar Farrel (Jurnal Multidisiplin Sahombu, 2026)
This study analyzes the representation of social stratification and resistance in James Cameron’s Titanic (1997). Beyond its image as a romantic tragedy, the film serves as a social commentary that exposes the inequality of early twentieth-century capitalist society. Through the contrasting lives of Jack Dawson and Rose DeWitt Bukater, Titanic illustrates how class distinctions influence human experience in terms of economy, culture, space, and gender. Using a qualitative descriptive method, the research analyzes selected scenes and dialogues as primary data. The study draws on the theories of Karl Marx, Max Weber, and Pierre Bourdieu to build a multidimensional understanding of class hierarchy and social resistance. The findings reveal that the film portrays social division through four interrelated aspects: economic disparity that limits access to comfort and survival, cultural boundaries marked by taste and manners, spatial segregation seen in the ship’s structure, and gender oppression as a means of maintaining hierarchy. Yet, Jack and Rose’s relationship symbolizes resistance to these barriers. Their emotional bond and moral courage show that love and humanity can transcend social limits, turning Titanic into a lasting reflection on justice, freedom, and human dignity.